Ecological role of benthic Vulnerable Marine Ecosystems (VMEs) indicator taxa on soft bottoms - Valeria Palummo; Giacomo Milisenda; Daniela Pica; Simonepietro Canese; Eva Salvati; Ludovica De Vincenzis; Pietro Battaglia; Nunziacarla Spanò; Teresa Romeo; Silvestro Greco (Scientific Reports)
Abstract Several aspects of the relationships between VME indicator taxa and associated fauna have been previously explored mainly on rocky habitat respect the soft bottom. However, the soft bottom hosts many VMEs indicator taxa for which the ecological role remained still unexplored. This habitat hosts many associated species, a lot of them also of commercial value making this habitat more vulnerable to fishing pressure. The present study investigates the variables that shape the distribution of associated fauna and their relationship with VME indicator species in the deep soft bottom of the Mediterranean Sea. Analyzing 74 ROV (Remotely Operated Vehicle) transects, VMEs indicator taxa and fish and crustacean density were extracted and analyzed together with environmental, morphological and anthropogenic variables. Through Redundancy Analysis (RDA), our findings reveal a clear relationship between several fish and crustacean species of commercial value and VME indicator taxa, like Isidella elongata and Pennatuloidea. By applying multivariate statistical approaches to an integrative dataset, the study provides a community-level perspective on the factors shaping fish and crustacean assemblages in potentially vulnerable habitats. The result highlights the necessity to better investigate the relationship among deep sea species in a wide prospectives to give powerful data for their conservation.